Communicative Language Teaching to improve speaking skills in senior students at Teodoro Gómez de la Torre high school in Ibarra during the academic year 2021-2022 - Morillo Tapia, Alisson Belén (2022)
To integrate Communicative language teaching in the improvement of speaking skills in senior students at Teodoro Gómez de la Torre high school in Ibarra during the academic year 2021-2022.